A history of Christian worship : ancient ways, future paths - Dallis, Tom; Daliis, Amy; Sauer, Bob; Witvliet, John D; Ensign Media (Firm) (Worcester, Pa : Gateway Films/ Vision Video, 2010)
For followers of Jesus Christ, worship has spanned over two thousand years to include a long and diverse history of sacred practices. The many ways in which the faithful have preserved and celebrated God's story is limited only by the human imagination. Ancient Ways, Future Paths is a six-part series that explores centuries of worship practices, as seen through the eyes of Protestant, Catholic and Orthodox churches and discussed by leading voices from a wide cross-section of Christians
Contents: pt. 1 The Word-- pt. 2 The Body
2 in 1
Documentary
Includes film trailers.
Historical consultant, John D. Witvliet.
Keywords: Worship -- History; Worship; Public worship -- History